2019
DOI: 10.1007/s11191-019-00051-3
|View full text |Cite|
|
Sign up to set email alerts
|

A Critical Review of Students’ and Teachers’ Understandings of Nature of Science

Abstract: There is widespread agreement that an adequate understanding of the nature of science (NOS) is a critical component of scientific literacy and a major goal in science education. However, we still do not know many specific details regarding how students and teachers learn particular aspects of NOS and what are the most important feature traits of instruction. In this context, the main objective of this review is to analyze articles from nine main science education journals that consider the teaching of NOS to K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 94 publications
3
50
0
24
Order By: Relevance
“…He concluded that open-ended questionnaires and interviews are the most appropriate measures to portray students' NOS perceptions. Abd-El-Khalick, as well as two more recent reviews (Azevedo & Scarpa, 2017;Cofré et al, 2019), found variants of the Views of Nature of Science Questionnaire (VNOS) (Lederman & O'Malley, 1990) the most widely used instruments. VNOS test instruments contain open-ended questions with slightly different examples, contexts and different levels of complexity depending on the age and background of the students.…”
Section: Assessing Students Nos Views In the Context Of Qpmentioning
confidence: 99%
“…He concluded that open-ended questionnaires and interviews are the most appropriate measures to portray students' NOS perceptions. Abd-El-Khalick, as well as two more recent reviews (Azevedo & Scarpa, 2017;Cofré et al, 2019), found variants of the Views of Nature of Science Questionnaire (VNOS) (Lederman & O'Malley, 1990) the most widely used instruments. VNOS test instruments contain open-ended questions with slightly different examples, contexts and different levels of complexity depending on the age and background of the students.…”
Section: Assessing Students Nos Views In the Context Of Qpmentioning
confidence: 99%
“…Los aspectos de la NdC más investigados en EP por los proponentes de esta conceptualización son (Cofré, Núñez, Santibáñez, Pavez, Valencia y Vergara 2019): (i) naturaleza provisional (la ciencia está sujeta a continuas revisiones y cambios); (ii) empirismo (la ciencia se construye a partir de evidencias del mundo natural); (iii) observaciones e inferencias (la ciencia se desarrolla a partir de observaciones del mundo natural e inferencias acerca de los fenómenos objeto de estudio); e (iv) imaginación y creatividad (la ciencia involucra la imaginación y la creatividad humana). Empleando esta conceptualización, numerosos estudios argumentan que estos aspectos de la NdC pueden ser comprendidos, empleando un enfoque de enseñanza explícito-reflexivo, inclusive por estudiantes del nivel elemental del sistema educativo (para dos revisiones de la literatura exhaustivas a este respecto, 2303-2 véase Akerson, Carter, Pongsanon y Nargund-Joshi 2019 y Cofré et al 2019).…”
Section: Naturaleza De La Cienciaunclassified
“…En primer lugar, para comprobar en qué medida algunos aspectos epistémicos de esta conceptualización, ampliamente promovidos e investigados en la etapa de EP, son útiles para detectar si la comprensión de la NdC está relacionada con una mayor valoración de la ciencia como un elemento cultural clave. En segundo lugar, porque existe una amplia bibliografía internacional que sugiere que los estudiantes de EP están preparados cognitivamente para comprender estas características epistémicas de la NdC (Akerson et al 2019;Cofré et al 2019); por tanto, la visión de consenso de Lederman y Lederman (2014) parecería ser una conceptualización de la NdC apropiada para la muestra de este estudio. Y, en tercer lugar, debido a que aún no existe bibliografía científica acerca de si los estudiantes de EP pueden comprender los aspectos no-epistémicos propuestos por García-Carmona y Acevedo-Díaz (2018), que sí han sido implementados eficazmente con estudiantes de Educación Secundaria Obligatoria (ESO) y Bachillerato (e.g., García-Carmona, Acevedo-Díaz y Aragón 2017).…”
Section: Naturaleza De La Cienciaunclassified
“…Much attention is paid to the problem of methodological training of students in methodological research, and authors raise the question of improving the quality of methodological training of teachers (Cofré et al, 2019).…”
Section: Introductionmentioning
confidence: 99%